Assessing the Future of Energy Security in Egypt - Atlam, Baher Mohamed; Rapiea, Asmaa Melegy (International Journal of Energy Economics and Policy, 2016)
This research aims to study the future of energy security in Egypt using System Dynamics approach. To achieve this objective, seven scenarios have been simulated for the period 2007-2030. The simulation results showed that, keeping other polices constant, raising the growth rate of new discoveries of oil and natural gas is the most effective policy for improving the future of energy security in Egypt, followed by removing energy subsidy and paying more investments in new and renewable energy respectively. In addition, targeting high economic growth rate is expected to have a negative effect on the future of energy security in Egypt, if it is not accompanied with more investments for increasing energy resources. On the other hand, the results showed that to improve energy security level and achieve sustainable economic development, a set of policies have to be adopted simultaneously to increase energy resources as well as rationalize energy consumption. Keywords: Energy Security– Energy Forecasting – Simulation Modeling JEL Classifications: F50, Q47, C63